EDUKASI PERPAJAKAN: UNDANG-UNDANG KETERBUKAAN INFORMASI KEUANGAN SEBAGAI SARANA MEMBANGUN KESADARAN BAYAR PAJAK MELALUI PENDIDIKAN PERGURUAN TINGGI YOGYAKARTA - Alfiatul Maulida; Siti Sumartiah (STIE Mandala Jember, 2022)
The large number of people who avoid taxes has made the government look for effective and efficient alternatives to enforce an orderly and legally correct manner, namely by issuing the Law on the Disclosure of Financial Information. The Law on Financial Information Disclosure was published on 23 August 2017. Access to financial information for tax purposes includes access to receive and obtain financial information in the context of implementing the provisions of laws and regulations in the field of taxation and the implementation of international tax treaties. This study aims to analyze how much influence tax education can have on building tax awareness, to analyze how much the Financial Information Disclosure Act is known and understood by prospective taxpayers and taxpayers, and to analyze the effect of the Law on the Disclosure of Financial Information to make Personal Taxpayers. pay taxes orderly. The research method used is Path Analysis. Keywords: tax education, disclosure of financial information, tax compliance funds